Immersed tunnels - Lunniss, Richard (CRC Press, Taylor & Francis Group, 2013)
Immersed tunnels have been around for more than a century but remain a relatively unknown form of tunnel construction. For waterway crossings they are an effective alternative to bored tunnels and bridges, particularly in shallower waters, soft alluvial soils, and earthquake-prone areas. Successful implementation requires a thorough understanding of a wide variety of civil engineering disciplines and construction techniques. Immersed Tunnels brings together in one volume all aspects of immersed tunnels from initial feasibility and planning, through design and construction, to operation and mai.